Gibson’s criteria: lectures and exercises for test pilots and flight test engineers - Hathaway, Christopher (Cranfield University, 2014)
Empire Test Pilots’ School (ETPS) trains experienced military pilots, engineers and civilian engineers as Test Pilots and Flight Test Engineers. Over a year, ETPS broadens the experience of each student through exposure to a wide variety of aircraft in addition to increasing their depth of understanding of how aerodynamics affect the handling qualities and ultimately the mission effectiveness of aircraft. The advent of computerized flight control systems has reduced the role of the aerodynamicist to a necessary one but no longer sufficient to achieve excellent handling qualities. Complex software programming performed by a control engineer is now required to realize this goal. Consequently, second order handling qualities criteria such as the longitudinal short period natural frequency and damping ratio are no longer strictly applicable to the significantly higher order modern flight control systems. Gibson’s Criteria was developed to provide control engineers the ability to design in excellent handling qualities from the outset, rather than waiting for pilots to identify failures during testing. While ETPS students are introduced to Gibson’s Criteria as part of the graduate course, the emphasis is on exposure and not an in-depth understanding. As the expense and time to develop modern high order aircraft grows exponentially, the importance of getting the handling qualities correct from the start only becomes more acute. It would be highly beneficial for graduates of ETPS to have a comprehensive understanding of how Gibson’s Criteria is applied early in software development to ensure excellent handling qualities are designed in early and effectively. This thesis is a survey of current material on Gibson’s Criteria and existing aircraft data / handling qualities problems formatted as a series of lectures and Matlab based problems designed to be given as part of the ETPS graduate course to achieve that level of knowledge.
Keywords: High Order Flight Control Systems; Short Period Pitch Response; Natural Frequency and Damping; Matlab; Designing in Excellent Handling Qualities; Modern Handling Qualities Criteria; Tornado; F-16; Hawk; A-7A